Pest biological control in spatial multispecies systems with Allee effect in the control agent population - Anjos, Lucas dos (2019)
In this thesis, we study the spatial dynamics of the three community modules in the context of biological pest control. In chapter 2 the study focuses on a predator-prey system with Allee effect and density dependent mortality in the predator. In chapter 3 a tritrophic food chain with Allee effect in the consumer population is studied, while in chapter 4 the analyzed community module consists of a tritrophic food web with intraguild predation and Allee effect in the consumer population. The central point in all these studies is to assess the interplay among Allee effect in the agent population, massive introduction of agent individuals and magnitude of agent diffusivity in the success/failure of pest biocontrol. Chapter 5 deals also with spatial dynamics of a predator-prey community module (without Allee effect in the predator population) but the emphasis rests upon the hydra effect in the predator population. The hydra effect is a counter-intuitive process whereby a population density level increases when its mortality rate is also increased. Nonetheless, it is important to remark that the results found therein related to hydra effect can also be applied to pest control. Chapter 6 reviews the main results of the whole work and proposes avenues of future research to extend pest biological control modeling.